Records and web content management - Saorín-Pérez, Tomás; Pastor-Sánchez, Juan-Antonio (Anuario ThinkEPI, 2012)
Review of major 2011 developments in the field of bibliographic cataloguing, document management and documentary languages. The use of content management systems for web publishing, the emergence of new approaches such as web experience management and the integration of web productivity components are analyzed.